Possible Complications of Ureteroscopy in Modern Endourological Era: Two-Point or “Scabbard” Avulsion - Andrius Gaizauskas; Marius Markevicius; Sergejus Gaizauskas; Arunas Zelvys (Case Reports in Urology)
Indication has led ureteroscopy to be a worldwide technique, with the expected appearance of multiple types of complications. Severe complications are possible including ureteral perforation or avulsion. Ureteral avulsion has been described as an upper urinary tract injury related to the action of blunt trauma, especially from traffic accidents, being the mechanism of injury, the result of an acute deceleration/acceleration movement. With the advent of endourology, that term is also applied to the extensive degloving injury resulting from a mechanism of stretching of the ureter that eventually breaks at the most weakened site, or ureteral avulsion is referred to as a discontinuation of the full thickness of the ureter. The paper presents a case report and literature review of the two-point or “scabbard” avulsion. The loss of long segment of the upper ureter, when end-to-end anastomosis is not technically feasible, presents a challenge to the urological surgeon. In the era of small calibre ureteroscopes these complications, due to growing incidence of renal stones will become more and more actual. Our message to other urologists is to know such a complication, to know the ways of treatment, and to analyse ureteroscopic signs, when to stop or pay attention.